Exploring the Relations between Peer Assessment, Self-Assessment, and Academic Achievement in School Science Experiment Course - Riana Nurismawati; Lilit Rusyati; Hanna Nurul Husna; Winda Hidayanti (Yayasan Keluarga Guru Mandiri, 2025)
Assessment has a pivotal role in education to evaluate students’ performance, with peer- and self-assessment as alternative tests to enhance the learning process. However, the links between self and peer assessment remain lacking in studies, in addition to academic achievement, particularly in science education. This study explores the correlations among peer assessment, self-assessment, and academic achievement (GPA) for higher education in School Science Experiment Courses. A correlational and comparative research design was conducted involving 96 preservice teachers. Data were analyzed using SPSS, with Spearman’s rank correlation for link analyses and the Kruskal-Wallis test with post-hoc comparisons for group differences. For overall scores, results described a strong relationship between peer and academic achievement and a weak correlation between peer- and self-assessment. No significant correlation was shown between self-assessment and GPA. For specific indicators, peer assessment is linked strongly with GPA all across indicators, while peer- and self-assessment correlated in six out of ten indicators, and the correlation between self-assessment and GPA lies in one indicator. Group comparisons revealed significant differences in peer- scores across High, average-, and low-achiever groups but no significant differences in self-scores. This relationship shows other alternative and innovative assessments that improve reflective skills and active learning.